Biobanks in cardiovascular disease research - A. M. Gusakova; E. S. Kravchenko; T. E. Suslova; S. V. Popov; A. A. Boshchenko (Кардиоваскулярная терапия и профилактика, 2025)
A systematic review of publications from the PubMed and eLibrary. ru databases, Biobanking and Biomolecular Resources Research Infrastructure — European Research Infrastructure Consortium (BBMRI-ERIC) and ClinicalTrials.gov studies was carried out for 15 years. The aim was to find priority areas for the use of biobanks in cardiology. The key areas of research on blood and heart tissue biobanks are the study of pathogenetic mechanisms, creation of innovative methods for diagnosis, treatment and prevention of cardiovascular diseases (CVDs). The use of modern technologies such as genomics, transcriptomics, proteomics and metabolomics allows identifying candidate markers, revealing new molecular targets for drug therapy, diagnostic and therapeutic approaches for CVD. One of the promising areas is the search and study of polygenic scores of CVD risk and predictors of adverse cardiovascular events. Analysis of the registry revealed another important area of biobank application — clinical trials, in which biobanks are a key resource of blood and tissue samples, as well as clinical, paraclinical, and socio-demographic data. Therefore, studies using biobank resources are necessary to study the pathogenetic mechanisms of CVD, identify new proteomic biomarkers and genetic factors, as well as to improve diagnostics, prevention and treatment.